Indian Social Stock Exchange as a Funding Avenue for Social Enterprises - Agarwal, Nishtha; Patavardhan, Roopa (Prabandhan: Indian Journal of Management, 2024)
Purpose : The growth of Indian social enterprises faces a significant obstacle, which is a lack of access to finance. The social stock exchange was recently launched to cater to this problem. This study explored the financial challenges the selected social enterprises faced in India and analyzed the performance of small and medium enterprises platforms. Methodology : Three variables were subjected to descriptive analysis: migration to the principal board, funds generated, and listings by small and medium-sized enterprises. Furthermore, market volatility was evaluated using the generalized autoregressive conditional heteroskedasticity (GARCH) model. To explore financial constraints, primary research entailed conducting in-depth interviews utilizing the case study technique with both for-profit and non-profit social companies. Findings : The findings from the study concluded that IPO financing significantly supported Indian SMEs. Additionally, social enterprises face significant financing challenges related to affordability, availability, and regulation. Social stock exchange presents a promising solution to these constraints. Practical Implications : The study has recommended defining social enterprises legally will help in strengthening the operating framework of a social stock exchange. The study emphasized the important role of finance in the viability of social enterprises by highlighting financial challenges. The findings provided useful information for various stakeholders to bridge the funding gap, thereby promoting the potential advantages of the social stock exchange platforms. Originality : The study addressed the research gap with an examination of small and medium enterprise platforms and the influence of the social stock exchange on social enterprise financing in India. Primary data from both for-profit and non-profit social entrepreneurs added a disaggregated dimension.